Islam’s rahmah (compassion) as applied by Hadrat Muhammad Rasulullah khatam un nabiyyin sallallahu ‘alaihi wa ‘ala alihi wa ashabihi wa sallam - Ushama, Thameem (Hamdard Foundation Pakistan, 2021)
This paper deals with rahmah (compassion and mercy) as practised by Prophet Hadrat Muhammad Rasulullah Khatam un Nabiyyin Sallallahu ‘alaihi wa ‘ala Alihi wa Ashabihi wa Sallam as an example for humanity that inspired his companions and was admired by others during his governance. Qualitative content analysis1 is applied to the traditional discourse on the subject using the text of The Holy Qur’an and its revered exegetes, and samples were taken from the Hadith corpus. The Biography of the Prophet Hadrat Muhammad Rasulullah Khatam un Nabiyyin Sallallahu ‘alaihi wa ‘ala Alihi wa Ashabihi wa Sallam finds its relevance to the contemporary context and the need of the hour. It studies the meaning of rahmah according to Muslim lexicographers and its English equivalent, “compassion.” Rahmah as ‘Ibad al-Rahman is examined as the Prophet’s (sal Allah-u-‘alaihi wa sallam) extension of Allah’s compassion and mercy for all creatures, emphasizing its need for peaceful coexistence and societal harmony. Examples of the Prophet’s (Sal Allah-u-‘alaihi wa sallam) governance concerning rahmah’s application to hypocrites, Jews, pagans, women, slaves, servants, animals, enemies, and prisoners of war.